Ibn Sina - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)
Abu Ali ai-Husain ibn Abdullah ib1 Sina (980-1 037 C.E .) was born in the village of Afshana near Bukhara which today is located in the far south of Russia.